ANALISIS KOMPARASI EFEKTIVITAS TAYANGAN IKLAN TELEVISI SITUS BELANJA ONLINE TOKOPEDIADAN BUKALAPAK PADAMASYARAKAT KOTA DENPASAR - Purwati, Sri Wulan; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT Television is familiar mediaforIndonesian people. Almost all of Indonesian people have television and tend to watch television. From the variety of content contained in television, advertising is one that is often encountered. As for most advertisers on television one of them is an online e-commerce service. Some of the active e-commerce advertising in 2016 on television is Tokopedia and Bukalapak. This research aim to measure comparison of the effectiveness of advertisements of Tokopedia and Bukalapak online shopping sites on television in Denpasar City. This research uses positivist paradigm with descriptive quantitative method. Sampling technique in this research is non-probability sampling and the method used is purposive sampling. Data were obtained by distributing questionnaires. The analytical technique used in the research through several stages of analysis technique average count, and test the average difference T-Test to attract the conclusions. This research showed there is no difference in the effectiveness of television advertising online shopping sites Tokopedia and Bukalapak in Denpasar city. Key Words :Bukalapak, Denpasar’s Citizen, Effectiveness, Television Advertisement, Tokopedia